2020
DOI: 10.1002/ppul.24780
|View full text |Cite
|
Sign up to set email alerts
|

Sleep‐disordered breathing and markers of morbidity in children and adolescents with cystic fibrosis

Abstract: Background: Studies have shown that sleep disorders occur in cystic fibrosis (CF) patients and may be present before daytime clinical manifestations.Objectives: To evaluate the presence of sleep disorders among children and adolescents with CF, attempting to identify associations with pulmonary function, nutritional status, days in hospital, and days taking antibiotics.Methods: Individuals with a diagnosis of CF aged between 6 and 18 years were included. Information on sociodemographic, clinical profile, hi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
30
2
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 16 publications
(34 citation statements)
references
References 37 publications
(57 reference statements)
1
30
2
1
Order By: Relevance
“…Although some studies have associated SDB with pulmonary function parameters in children with CF, no such correlation has yet been established for patients with PCD 6,29–32 . Likewise, we did not find any associations between sleep disorders and clinical parameters of children with lung disease.…”
Section: Discussioncontrasting
confidence: 94%
“…Although some studies have associated SDB with pulmonary function parameters in children with CF, no such correlation has yet been established for patients with PCD 6,29–32 . Likewise, we did not find any associations between sleep disorders and clinical parameters of children with lung disease.…”
Section: Discussioncontrasting
confidence: 94%
“…However, other studies 18,19 have indicated that patients with CF tend to lessen the importance of exercises on daily routine and, therefore, adherence to exercises are lower compared with pancreatic enzymes and antibiotics therapies. [19][20][21] The purpose of this study was to describe the level of adherence and the barriers to general and respiratory exercises reported by individuals diagnosed with CF. The specific research questions were: The findings may help the identification of individuals with CF who are less likely to exercise and, therefore, help guide clinical practice by suggesting strategies to increase adherence to exercises.…”
Section: Introductionmentioning
confidence: 99%
“…The frequency of OSA is high among young children with CF, and the presence of both these conditions together is associated with lower nocturnal oxygen saturations than in children with CF alone 16 . A recent study demonstrated that the prevalence of OSA and nocturnal hypoxemia in CF is close to 30% in children and adolescents 40 …”
Section: Sleep‐disordered Brreathing Across the Lifespanmentioning
confidence: 99%
“…It is important to note that the definition of hypoxemia varies in studies in the literature, but the AASM defines nocturnal hypoxemia as oxygen saturation ≤90% in children and ≤88% in adults for >5 minutes 32 . Higher total sleep time spent with oxygen saturation of <90% is associated with worse pulmonary function in children 40 …”
Section: Sbd: Screening Tools and Definition Of Key Termsmentioning
confidence: 99%